Pentapeptide-Zinc Chelate from Sweet Almond Expeller Amandin Hydrolysates: Structural and Physicochemical Characteristics, Stability and Zinc Transport Ability In Vitro - Jiangning Zhang; Zheng Ye (Molecules, 2022)
To promote the application of almond expellers, sweet almond expeller globulin (amandin) was extracted for the preparation of bioactive peptides. After dual enzymatic hydrolysis, Sephadex G-15 gel isolation, reverse-phase high-performance liquid chromatography purification and ESI-MS/MS analysis, two novel peptides Val-Asp-Leu-Val-Ala-Glu-Val-Pro-Arg-Gly-Leu (1164.45 Da) and Leu-Asp-Arg-Leu-Glu (644.77 Da) were identified in sweet almond expeller amandin hydrolysates. Leu-Asp-Arg-Leu-Glu (LDRLE) of excellent zinc-chelating capacity (24.73 mg/g) was selected for preparation of peptide-zinc chelate. Structural analysis revealed that zinc ions were mainly bonded to amino group and carboxyl group of LDRLE. Potential toxicity and some physicochemical properties of LDRLE and Val-Asp-Leu-Val-Ala-Glu-Val-Pro-Arg-Gly-Leu (VDLVAEVPRGL) were predicted in silico. The results demonstrated that both LDRLE and VDLVAEVPRGL were not toxic. Additionally, zinc solubility of LDRLE-zinc chelate was much higher than that of zinc sulphate and zinc gluconate at pH 6.0–10.0 and against gastrointestinal digestion at 37 °C (p < 0.05). However, incubation at 100 °C for 20–60 min significantly reduced zinc-solubility of LDRLE-zinc chelate. Moreover, the chelate showed higher zinc transport ability in vitro than zinc sulphate and zinc gluconate (p < 0.05). Therefore, peptides isolated from sweet almond expeller amandin have potential applications as ingredient of zinc supplements.